Distribution of Manganese, Iron, Copper, Lead and Zinc in Water and Sediment of Kelang Estuary - Law , A. T.; Singh, G. (1986)
A study was conducted on the distrubution of manganese, iron, copper, lead and zinc in the water and sediment of Kelang estuary in 1981. The mean total levels of manganese, iron, copper, lead and zinc in the estuarine water were 27.1 pgl1,106.5 gil, '10.0 pgl1, 4.1 Ilg/l and 17.9 Ilg11 respectively. For the dissolved copper, lead and zinc, the values were 4.3 pg/l, 1.6 Ilg/l and 3.9 pgI l respectively. In the estuarine sediment, the copper, lead and zinc contents were 1.92, 0.48 and 5.43 ppm wet sediment respectively. The levels of these heavy metalized water and sediment were comparable to the values reported for other estuarise. The copper and zinc levels were similar to those found in the world oceans, The results indicate that Kelang estuary is polluted with lead, manganese and iron. However, levels of these heavy, metals may still be considered safe for aquaculture, if the farm is located at least 10 km away from the Rivers mouth.